1968
DOI: 10.1113/expphysiol.1968.sp001971
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Volatile Fatty Acids, Tritiated Water and Antipyrine From the Abomasum of Goats

Abstract: In conscious goats the abomasum was isolated temporarily from the rest of the gastro-intestinal tract by means of balloons, or a double by-pass or a snare around the pylorus. Abomasal contents, rumen fluid or a saline solution were given into the abomasum. Altogether forty experiments were done on four goats.The absorption of acetic acid, propionic acid, butyric acid, tritiated water (HTO) and antipyrine (AP) from the abomasum was measured. For comparison of the absorption rates, the data were given as clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Greater epithelium thickness in the pyloric region of the abomasum of BUT animals is in line with the previously reported trophic effect of butyrate on the stomach tissue mass in monogastric animals (Kotunia et al, 2004;Mazzoni et al, 2008). It was also shown that butyrate is absorbed from the abomasum (Engelhardt et al, 1968;Williams et al, 1968). When absorbed, butyrate is most likely completely oxidized by the abomasal epithelium (Guilloteau et al, 2009;Guilloteau et al, 2010a).…”
Section: Discussionsupporting
confidence: 87%
“…Greater epithelium thickness in the pyloric region of the abomasum of BUT animals is in line with the previously reported trophic effect of butyrate on the stomach tissue mass in monogastric animals (Kotunia et al, 2004;Mazzoni et al, 2008). It was also shown that butyrate is absorbed from the abomasum (Engelhardt et al, 1968;Williams et al, 1968). When absorbed, butyrate is most likely completely oxidized by the abomasal epithelium (Guilloteau et al, 2009;Guilloteau et al, 2010a).…”
Section: Discussionsupporting
confidence: 87%
“…16 ' 32,47 Nonetheless, the abomasum has the capacity to absorb short-chain fatty acids and Ash 15 and subsequent investigators have shown that, of the short-chain fatty acids which reach the abomasum, a high proportion is absorbed there. 72,151,301 Furthermore, many of the absorptive characteristics of the system operating within the rumen, e.g. The latter workers also demonstrated that, despite the low concentrations of short-chain fatty acids that were found in the abomasum, the absorption occurring there was quanti tatively significant and could supply up to 10% of the basal metabolic requirements of the animal.…”
Section: Absorption and Metabolism Of Short-chain Fatty Acidsmentioning
confidence: 99%
“…Badawy et al, 11 using insoluble ash as an inert marker, estimated that in the sheep, 74% of the shortchain fatty acids present in the abomasal contents were absorbed, while Engelhardt et al, 12 using the surgically isolated abomasum of the goat, gave a figure of 90%. 72 Indeed, it was suggested by these authors that the low concentrations of the short-chain fatty acids in the abomasal contents were due more to the rapid absorption occurring there than to prior absorption from the omasum.…”
Section: Absorption and Metabolism Of Short-chain Fatty Acidsmentioning
confidence: 99%
“…Ruminally produced propionic acid must be absorbed across the epithelium in order to enter the animal. Previous reports indicate that 76 to 95% of ruminally produced propionic acid is absorbed in the rumen; however, those studies were conducted with sheep (Gray, 1947;Weston and Hogan, 1968;Williams et al, 1968) or in animals whose normal rumen conditions were not maintained (Masson and Phillipson, 1951;von Engelhardt et al, 1968). The capacity of the rumen to remove propionate at elevated levels of production characteristic of today's high producing ruminants remains unknown.…”
mentioning
confidence: 99%